PENGARUH PATRIOTISME, TATA KELOLA PUBLIK, DAN LABA USAHA TERHADAP KEPATUHAN PAJAK PENGHASILAN BADAN USAHA KECIL DAN MENENGAH (Studi pada Wajib Pajak Badan Usaha Kecil dan Menengah di Semarang) - Zukhruf Indira Asatri; Agus Purwanto (Diponegoro Journal of Accounting, 2022)
This study aims to analyze the level of sales tax compliance among small and middle enterprises in Semarang. The study consists of three independent variable and a dependent variable. The independent variable is patriotism, public governance, and profit. Whereas the dependent variable is income tax compliance.The method that use in this study is purposive sampling, where all the small and medium enterprises are listed on the Ijin Usaha Mikro Kecil (IUMK) Semarang website. From the application of that method obtained 53 small and medium enterprises, which in turn, through a quetionnaire received 45 that fit the criteria of research samples. The criteria is include: 1. Listed on the Ijin Usaha Mikro Kecil Semarang’s website, 2. Have the corporate taxpayer identification number, 3. Been operating at least for three years, 4. Earning per share less than 50 billion.Data analysis on research is measured using Partial Least Squares (PLS) with reflective construct. The results of this study indicate that there is a positive influence of the patriotism, public goverment, and operating profit of sales tax complience.